Toward Safer Pregnancies: Usability evaluation of a prototype application for monitoring and controlling hypertensive disorders in pregnancy - Nielsen Pimentel, Mel Imanol; Villarreal, Vladimir; Muñoz Arracera, Lilia Esther; González Gómez, Joseph Antony; Domínguez Perez, Danilo (Ingeniería Solidaria, 2023)
Introduction: Hypertensive disorders in pregnancy pose global health challenges. Maternal mortality rates in Panama due to preeclampsia and eclampsia have increased. A mobile application is introduced to monitor and control these disorders. Problem: Hypertensive disorders in pregnancy pose a risk to maternal health. Panama’s healthcare initiatives have shown progress, but there are still gaps in maternal care. Novel technologies may help address these gaps. Objective: The goal is to evaluate a prototype mobile app for managing hypertensive disorders in pregnancy. Research focuses on usability, including navigation, design-task correlation, acceptability, and user perspectives. Methodology: The Design Science Research Methodology (DSRM) guides the study through problem identification, motivation, and software artifact development. The evaluation involves 32 participants engaging in tasks and standardized questionnaires, including the System Usability Scale (SUS) and User Experience Questionnaire (UEQ). Tasks assess the app’s usability, while questionnaires provide comprehensive insights into user experiences. Results: Users generally have positive interactions and favorable perceptions. However, there are challenges with task completion, particularly with interface intuitiveness. Conclusion: The app for monitoring hypertensive disorders has shown positive user experiences and usability. However, there are challenges and user feedback that need to be addressed for refinement and effectiveness in supporting maternal health during pregnancy. Limitations: The study focuses only on the prototype evaluation phase and may need further iterations to address challenges. The participant pool’s limitations may impact generalizability. Ongoing improvements are crucial to meet evolving user needs and technological advancements. Originality: This article contributes originality by presenting a novel mobile application prototype for managing hypertensive disorders in pregnancy. The use of DSRM for development and comprehensive usability assessments with standardized tools adds to the originality, providing valuable insights for future advancements in maternal healthcare technology.